Fadiga em dormentes de concreto reforçados com fibras de aço - Bastos, Paulo S.S. [UNESP]; Pinheiro, Libânio M. [UNESP] (My University, 2001)
A prestressed concrete monoblock railroad tie was designed to attend the characteristics of a Brazilian railroad track with 1,600 mm gauge and 320 kN axle load. Concrete ties specimens were manufactured without and with steel fibers in a volume fraction of 60 kg/m3 (0.76 % by volume), and three different initial prestress forces. Static and fatigue tests were carried out on the ties. Static tests showed that steel fibers increase the first crack and ultimate bending moments, increase significantly the slip force of the prestressing tendons, reduce crack width, add higher ductility to the ties and decrease the stress in the prestressing tendons. Under dynamic loading the steel fibers decreased the stress in the prestressing tendons by about 50%, which improved significantly the fatigue strength of the tie. A tie without fibers failed after only 150,000 cycles. However, a similar tie, with fibers, resisted 3,000,000 cycles without suffering fatigue failure.
Concrete railroad ties reinforced with steel fibers to fatigue loading
Keywords: Concrete tie; Fatigue; Precast concrete; Prestressed concrete; Steel fibers; Cracks; Dynamic loads; Failure (mechanical); Fatigue testing; Fiber reinforced materials; Railroad ties; Steel; Stress analysis; Volume fraction; Monoblock railroad ties; Reinforced concrete